1995
DOI: 10.2307/2082425
|View full text |Cite
|
Sign up to set email alerts
|

Beyond SES: A Resource Model of Political Participation

Abstract: This paper develops a resource model of political participation. The resources considered are time, money, and civic skills—those communications and organizational capacities that are essential to political activity. These skills are not only acquired early in life but developed in the nonpolitical institutional settings of adult life: the workplace, organizations, and churches and synagogues. These resources are distributed differentially among groups defined by socioeconomic status. A two-stage least squares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
1,371
7
93

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,087 publications
(1,576 citation statements)
references
References 21 publications
53
1,371
7
93
Order By: Relevance
“…Multiple studies have found that informed citizens are more likely to be involved in civic and political action and to engage in participatory activities such as voting, attending political meetings, contacting officials, and protesting (Neuman 1986;Zaller 1992;Brady et al 1995;Gerber and Green 2000). Studies have also…”
Section: Relation To the Literaturementioning
confidence: 99%
“…Multiple studies have found that informed citizens are more likely to be involved in civic and political action and to engage in participatory activities such as voting, attending political meetings, contacting officials, and protesting (Neuman 1986;Zaller 1992;Brady et al 1995;Gerber and Green 2000). Studies have also…”
Section: Relation To the Literaturementioning
confidence: 99%
“…Immigration generation and age are both related to ethnic minority political engagement and integration Maxwell, 2010). Higher education is associated with more conventional and nonconventional political participation (Brady, Verba, & Schlozman, 1995), and with some differences in political attitudes. I control for ethnicity, because not all Muslims in the UK have the same ethnic background, and Pakistani origin Muslims have stronger feelings of opposition to Afghanistan than other Muslim groups .…”
mentioning
confidence: 99%
“…Civic knowledgeable adults are more likely to grasp political issues and support political candidates that represent their best interest (Bennet, 2003;Delli Carpini & Keeter, 1996). In addition, civic knowledge provides the foundational knowledge and skills that allow people to become active members of their community (Brady, Verba & Schlozman, 1995). Acquiring these knowledge skills may propel students to greater civic participation.…”
Section: Civic Knowledgementioning
confidence: 99%